A Case of Central Venous Catheter-Related Bacteremia Caused by Enterococcus gallinarum - Ning Xu; Lei Zhu; Liyan Xiong; Jingjing Huo; Bin Wang; Xianyan Wu; Rui Tao; Qi Sa (Case Reports in Infectious Diseases)
A chicken farmer with cirrhosis and renal failure presented with an unusual case of catheter-related bacteremia. Testing with the VITEK® 2 Compact system, MALDI-TOF mass spectrometry, and 16S rDNA sequencing identified the pathogen as E. gallinarum. This case demonstrates the importance of maintaining a high level of contextual awareness in patients exposed to avian species to make an informed diagnosis and provide prompt treatment.